Diagnostic Accuracy of Fine Needle Aspiration Cytology in Soft Tissue Sarcomas - Soffia Khursheed, Hijab Shah, Mariam Asim (Journal of Rawalpindi Medical College, 2018)
Background: To study diagnostic validity of fine needle aspiration cytology in soft tissue sarcoma. Methods: In this descriptive study patients of all ages and both gender with obvious soft tissue swellings and patient in whom both FNAC followed by histopathology, were included. Cases with obvious inflammatory lesions were excluded from the study. Immunohistochemistry was employed where required.The diagnosis made on FNAC was then compared with the diagnosis made on histopathology. Results: Mean age of the patients was 28 years± 16yrs. Lower extremity tumours were seen in 65%. Most common soft tissue sarcoma on FNAC was spindle cell sarcoma (11 cases) followed by round cell sarcoma(10 cases). Subsequent histopathology of cases showed 55% of benign soft tissue tumours and 45% of soft tissue sarcomas. Hence there were 4 false negative cases and one false positive case on cytology. On comparing with histopathological correlation diagnostic accuracy of FNAC in diagnosing soft tissue sarcoma came out to be 92.3%.The sensitivity and specificity of FNAC in soft tissue sarcoma was 86.2 % and 97.2% respectively. Conclusion: FNAC is a useful procedure in preoperative diagnosis of benign and malignant soft tissue tumours , with a high sensitivity, specificity and diagnostic accuracy in soft tissue sarcomas.